2023
DOI: 10.1242/dmm.049810
|View full text |Cite
|
Sign up to set email alerts
|

A kidney resident macrophage subset is a candidate biomarker for renal cystic disease in preclinical models

Abstract: Although renal macrophages have been shown to contribute to cystic kidney disease in PKD animal models, it remains unclear if there is a specific macrophage subpopulation involved. Here we analyze changes in macrophage populations during renal maturation in association with cystogenesis rates in conditional Pkd2 mutant mice. We demonstrate that CD206+ resident macrophages are minimal in a normal adult kidney but accumulate in cystic areas in adult-induced Pkd2 mutants. Using Cx3cr1 null mice, we reduced macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This response may be impaired, as evidenced by reduction in VEGFR expression in pericystic endothelium, a finding also reflected by previous work showing loss of VEGF signalling as a feature of PKD rodent models (29, 89). Alternatively pericystic endothelium, in its altered phenotypic state, could contribute to further inflammation and fibrotic remodelling, by driving the recruitment and activation of adjacent cells, including fibroblasts (17) or macrophages (90, 91). In any case, these vessels are associated with a decline in local cortical perfusion within the kidney, as we demonstrated using ASL of Pkd1 RC/RC mouse kidneys at the early, 3-month stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This response may be impaired, as evidenced by reduction in VEGFR expression in pericystic endothelium, a finding also reflected by previous work showing loss of VEGF signalling as a feature of PKD rodent models (29, 89). Alternatively pericystic endothelium, in its altered phenotypic state, could contribute to further inflammation and fibrotic remodelling, by driving the recruitment and activation of adjacent cells, including fibroblasts (17) or macrophages (90, 91). In any case, these vessels are associated with a decline in local cortical perfusion within the kidney, as we demonstrated using ASL of Pkd1 RC/RC mouse kidneys at the early, 3-month stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…CD45 + renal leukocytes were selected, while granulocytes (using Ly6G staining) and CD11B – cells were excluded. Gating was then set to distinguish between F4/80 – (early infiltrating monocytes), F4/80 int (BM-derived renal macrophages), and F4/80 hi (kidney-resident macrophages [KRM]) cells, as described ( Supplemental Figure 13 ) ( 67 , 69 ). There was an expected increase in total CD45 + , CD11B + , and CD45 + CD11B + nongranulocyte (ly6G – ) mononuclear cells after IRI-AKI, there was no difference in total cell numbers between PEPCK Cre + and Cre – kidneys ( Supplemental Figure 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this small group of ADPKD patients, baseline urinary CD14 levels (but not GFR) significantly correlated with a two-year rate of TKV change, indicating that urinary CD14 level could serve as a predictor of ADPKD outcome. Despite the strong correlations detected by flow cytometry analyses in these studies (93)(94)(95), the reported results are limited by small cohorts of ADPKD patients and, as a consequence, lack of the multiple covariate effects evaluation. Therefore, additional flow cytometry analyses in larger, well-characterized cohorts of ADPKD patients are required for validation of the reported findings and drawing conclusions.…”
Section: Urine Inflammatory Glomerular and Tubular Damage Biomarkersmentioning
confidence: 87%
“…Zimmerman et al (93) reported an increased total number of intrarenal CD4 and CD8 T cells and a correlation between urinary CD4+ T cell count and annual eGFR decline over 5 years in a small cohort of ADPKD patients (n = 30), suggesting this novel marker as a candidate prognostic biomarker in ADPKD and supporting the proposed role of T cells in ADPKD pathogenesis. Li et al (94) reported increased number of CD206 + macrophages in kidneys and urine from 30 ADPKD patients. The number of CD206 + macrophages correlated with the annual eGFR decline, indicating its utility for assessing disease activity and predicting renal function decline in ADPKD patients.…”
Section: Urine Inflammatory Glomerular and Tubular Damage Biomarkersmentioning
confidence: 99%